Polyaniline/CeO2 nanocomposites as corrosion inhibitors for improving the corrosive performance of epoxy coating on carbon steel in 3.5% NaCl solution - Lei, Yanhua; Qiu, Zhichao; Tan, Ning; Du, Hailiang; Li, Dongdong; Liu, Jingrong; Liu, Tao; Zhang, Weiguo; Chang, Xueting (Progress in organic coatings, 2020)
•∼6 nm CeO2 particles were uniformly dispersed into PANI matrix.•LEIS and salt spray tests were performed to evaluate the corrosion performance of coatings.•PANI/CeO2 in epoxy coating exhibits a synergetic effect of diffusion barrier and self-healing behaviors. Polyaniline/cerium dioxide (PANI/CeO2) nanocomposite (NPs) was synthesized by in situ polymerization of aniline in the presence of CeO2 NPs. Various analytical facilities, i.e., powder X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), and high-resolution transmission electron microscopy (HRTEM), were utilized to characterize the synthesized CeO2 and PANI/CeO2 NPs. The coatings prepared from the synthesized PANI/CeO2 NPs exhibited excellent corrosion resistance that was superior to epoxy coatings added with PANI in NaCl solution. The exceptional improvement of corrosion protection performance of the PANI/CeO2 /epoxy coatings is associated with the synergetic protection of the enhancement of the protective barrier due to the role of CeO2 NPs and PANI against the diffusion of aggressive ions (e.g., Cl−) and the improvement of self-healing protection attributed to the redox behavior of PANI. Thus, the hybrid PANI/CeO2 NPs are considered as the best route to enhance the protection performance of the epoxy coatings on carbon steel.